Alternate Partial Root-Zone Drip Nitrogen Fertigation Reduces Residual Nitrate Loss While Improving the Water Use but Not Nitrogen Use Efficiency - Liu, Rui; Zhu, Peng-Fei; Wang, Yao-Sheng; Chen, Zhen; Zhu, Ji-Rong; Shu, Liang-Zuo; Zhang, Wen-Ju (Frontiers in Plant Science, 2021)
The efficient utilization of irrigation water and nitrogen is of great importance for sustainable agricultural production. Alternate partial root-zone drip irrigation (APRD) is an innovative water-saving drip irrigation technology. However, the coupling effects of water and nitrogen (N) supply under APRD on crop growth, water and N use efficiency, as well as the utilization and fate of residual nitrates accumulated in the soil profile are not clear. A simulated soil column experiment where 30–40 cm soil layer was 15NO3-labeled as residual nitrate was conducted to investigate the coupling effects of different water [sufficient irrigation (W1), two-thirds of the W1(W2)] and N [high level (N1), 50% of N1 (N2)] supplies under different irrigation modes [conventional irrigation (C), APRD (A)] on tomato growth, irrigation water (IWUE) and N use efficiencies (NUE), and the fate of residual N. The results showed that, compared with CW1N1, AW1N1 promoted root growth and nitrogen absorption, and increased tomato yield, while the N absorption and yield did not vary significantly in AW2N1. The N absorption in AW2N2 decreased by 16.1%, while the tomato yield decreased by only 8.8% compared with CW1N1. The highest IWUE appeared in AW2N1, whereas the highest NUE was observed in AW2N2, with no significant difference in NUE between AW2N1 and CW1N1 at the same N supply level. The 15N accumulation peak layer was almost the same as the originally labeled layer under APRD, whereas it moved 10–20 cm downwards under CW1N1. The amount of 15N accumulated in the 0-40 cm layer increased with the decreasing irrigation water and nitrogen supply, with an increase of 82.9–141.1% in APRD compared with that in CW1N1. The utilization of the 15N labeled soil profile by the tomato plants increased by 9–20.5%, whereas the loss rate of 15N from the plant-soil column system decreased by 21.3–50.1% in APRD compared with the CW1N1 treatment. Thus, APRD has great potential in saving irrigation water, facilitating water use while reducing the loss of residual nitrate accumulated in the soil profile, but has no significant effect on the NUE absorbed.